Porous carbon material for positive electrode of lithium-sulfur battery and preparation method of porous carbon material

The MOF-derived carbon material SOM-Ce with an ordered porous morphology was synthesized by the template method, which solved the problems of low conductivity and insufficient adsorption-catalytic capacity in the positive electrode of the lithium-sulfur battery, and achieved the effect of improving the electrochemical performance and cycle life of the lithium-sulfur battery.

CN119569023AActive Publication Date: 2025-03-07CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411576164.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-07
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing metal organic frame (MOF) materials have problems such as small pore size, low conductivity and weak adsorption-catalytic capacity in the positive electrode of lithium sulfur batteries, which hinders the application of MOF-based materials in lithium sulfur batteries.

Method used

The MOF-derived carbon material with an ordered porous morphology was synthesized by the template method, and the PS template was formed by polymerization of sodium hydroxide-washed styrene and polyvinylpyrrolidone. Then, cerium was introduced during the growth of MOF, and finally the porous MOF-derived carbon material SOM-Ce was obtained by high-temperature carbonization.

Benefits of technology

The conductivity and electrochemical performance of the cathode material of lithium sulfur battery are improved, the utilization rate of active substances is enhanced, the shuttle effect is suppressed, and the cycle life of lithium sulfur battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569023A_ABST
    Figure CN119569023A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon material for a positive electrode of a lithium-sulfur battery and a preparation method of the porous carbon material, and relates to the technical field of material preparation, PS templates with different particle sizes are utilized to perform pore forming on MOF, Ce element is loaded for modification, and finally high-temperature carbonization is performed to synthesize an MOF derived carbon material with an ordered porous morphology. And the porous structure can accommodate more active substance sulfur / lithium sulfide of the lithium-sulfur battery, and also can expose more active sites, so that the utilization rate of the active center is improved. The structural stability and the conductivity can be improved through carbonization, and Ce atoms serving as an active center can achieve the electrochemical activity of catalytic electrochemical reaction by receiving and giving electrons due to the unique characteristics of the Ce atoms. Meanwhile, the cerium element is high in polarity and can provide a powerful polar adsorption effect, and adsorption and catalytic conversion combination is achieved. The utilization rate of active substances is effectively improved, the shuttle effect is inhibited, and the electrochemical performance and the cycle life of the lithium-sulfur battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to a porous carbon material for a lithium-sulfur battery positive electrode and a preparation method thereof. Background Art

[0002] Lithium-sulfur batteries have the advantages of high theoretical energy density, high theoretical specific capacity, low price, and environmental friendliness, and have become the next generation of energy storage systems that researchers focus on. Lithium-sulfur batteries have obvious advantages, but their inherent disadvantages cannot be ignored, including low positive electrode conductivity, lithium dendrite growth, and shuttle effect, which are problems that lithium-sulfur batteries must overcome in order to be commercialized.

[0003] Metal organic framework (MOF) materials have shown potential application value in lithium sulfur battery (Li-S) positive electrode materials due to their unique structure and performance characteristics. MOF materials have the advantages of high specific surface area, adjustable pore structure and easy functionalization. These characteristics enable MOF to provide abundant active sites, improve sulfur loading and dispersion, and enhance the kinetics of electrochemical reactions. For example, patent publication number CN109904455B discloses a lithium sulfur battery positive electrode carrier material and its preparation method, the material is composed of multi-layer porous carbon sheets and CoS2 nanoparticles; the multi-layer porous carbon sheets are formed by layer-by-layer assembly of carbon nanosheet units, and the porous carbon derived from the metal organic framework material in the carbon nanosheet unit grows densely on both sides of reduced graphene oxide; CoS2 nanoparticles are embedded in the porous carbon nanosheets, and the particle size of CoS2 nanoparticles is 5-35nm. It has a large specific surface area and rich porous structure, can physically adsorb polysulfides, effectively slow down the volume expansion of polysulfides, and can promote the rapid transmission of ions and electrons.

[0004] Based on the above search and in combination with the prior art, it is found that the existing metal organic framework (MOF) materials have small pore sizes that make it difficult to penetrate electrolytes and active substances, the electrical conductivity needs to be improved, and the adsorption-catalytic ability is weak. These problems hinder the application of MOF-based materials in lithium-sulfur batteries. Therefore, a porous carbon material for the positive electrode of a lithium-sulfur battery and a preparation method thereof are proposed to improve the above problems. Summary of the invention

[0005] The purpose of the present application is to provide a porous carbon material for a lithium-sulfur battery positive electrode and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present application provides the following technical solution: a method for preparing a porous carbon material for a positive electrode of a lithium-sulfur battery, comprising the following steps:

[0007] S1, styrene washed with sodium hydroxide and polyvinyl pyrrolidone are polymerized into PS under the condition of oil bath;

[0008] S2, soaking PS in methanol solution of cerium nitrate and methanol solution of zinc nitrate + dimethylimidazole;

[0009] S3, immersing the treated PS in a mixed solution of methanol and ammonia water to grow MOF;

[0010] S4. After soaking in THF or DMF and centrifuging to remove PS, a white powder is obtained, and the obtained white powder is annealed in a tube furnace to obtain porous MOF-derived carbon SOM-Ce.

[0011] As a further supplement to this solution, the preparation method of PS comprises the following steps:

[0012] S11, 50 mL of styrene and 15 mL of sodium hydroxide were uniformly mixed in a separatory funnel to remove the inhibitor and acidic impurities therein, and then washed with water three times to remove the residual sodium hydroxide;

[0013] S12, adding the treated styrene into a 1000 mL three-necked flask, adding 400 mL of distilled water and 1.7 g of polyvinyl pyrrolidone, stirring under the condition of bubbling in an inert atmosphere, then keeping warm under the condition of heating in an oil bath, then adding 60 mL of 10% potassium persulfate as an initiator, and performing a polymerization reaction under heating in an oil bath;

[0014] S13. The white suspension after the polymerization reaction was filtered and washed with distilled water, and then the residual moisture was removed in a 40° C. forced air oven.

[0015] As a further supplement to this scheme, in S11, the concentration of sodium hydroxide is 5-15%, and the volume ratio of styrene to sodium hydroxide is (1.5-8):1;

[0016] In S12, the mass ratio of polyvinyl pyrrolidone to potassium persulfate is (2-4):1.

[0017] As a further supplement to this scheme, in S12, the bubbling time of the inert atmosphere is 10-30 minutes, the inert atmosphere is argon or nitrogen, and the insulation oil bath time before adding the initiator is 30-60 minutes to ensure the temperature stability in the system.

[0018] As a further supplement to this scheme, in S12, the heating temperature of the polymerization reaction under oil bath heating is 80-95°C, the reaction time is 22-26h, and the magnetic stirring speed is 200-600r / min.

[0019] As a further supplement to this scheme, in S2, the ratio of zinc nitrate to dimethylimidazole is 1:(1-1.25), the methanol solution is 50-100 mL, the concentration of nitrate is 0-32 mmol / L, the nitrate includes one or more of cerium nitrate, lanthanum nitrate, indium nitrate, and iron nitrate, and the concentration of nitrate in methanol is 5-50 mg / mL, the immersion time is 2-8 h, and the drying temperature after immersion is 40°C for 8-24 h.

[0020] As a further supplement to this scheme, in S3, the ratio of methanol to ammonia water is (0-60 mL): (0-60 mL), and ultrasound is used for 3-5 min to accelerate the nucleation and growth of the MOF material at the beginning of immersion.

[0021] As a further supplement to this scheme, in S4, the amount of THF or DMF used is 200-1000 mL, the soaking time is 20-30 h, the solvent for the subsequent centrifugation is THF or DMF, the number of centrifugation is 5-6 times, the speed is 5000-6000 r / min, each time is 5-8 min / , the drying temperature is 110°C, and the drying time is 12-24 h.

[0022] As a further supplement to this solution, in S4, the carbonization temperature of the annealing is 800-1000° C., the heating rate is 1-5° C. / min, the calcination time is 2-4 h, and the atmosphere is argon or nitrogen.

[0023] A porous carbon material for a lithium-sulfur battery positive electrode is prepared according to the method for preparing the porous carbon material for a lithium-sulfur battery positive electrode.

[0024] In summary, the technical effects and advantages of the present invention are as follows:

[0025] 1. The present invention uses a template method to synthesize a MOF-derived carbon material with an ordered porous morphology. Its porous structure can accommodate more sulfur / lithium sulfide, the active material of the lithium-sulfur battery, and can also expose more active sites, thereby improving the utilization rate of the active center. Due to its unique characteristics, the Ce atom as the active center can switch freely between +3 valence and +4 valence, and realize catalytic electrochemical reactions by receiving and giving electrons. At the same time, the polarity of the cerium element is higher than that of commonly used transition metal elements (including Ni, Co, Mn, Fe, etc.), which can provide a strong polar adsorption effect, realize the combination of adsorption + catalytic conversion, improve the utilization rate of active substances, inhibit the shuttle effect, and improve the electrochemical performance and cycle life of lithium-sulfur batteries.

[0026] 2. The preparation method of the present invention is scientific, reasonable, easy to implement and low-cost. The obtained ordered porous cerium-doped MOF has simple synthesis and easy-to-adjust coordination composition. Li2S / SOM-Ce releases high specific capacities of 765, 715, and 698 mAh / g in the first cycle at 0.1C, respectively. The charge and discharge efficiencies in the first three cycles are 93.5%, 97.6%, and 98.9%, respectively, which effectively improves the utilization rate of active materials, inhibits the shuttle effect, and improves the electrochemical performance and cycle life of lithium-sulfur batteries, providing an important reference for the next generation of high-performance lithium sulfide-based lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0028] Figure 1 (ab) SEM images and (ef) elemental mapping images of the prepared polystyrene beads (PS);

[0029] Figure 2 SEM images of the prepared (ac) cerium-doped MOF grown in PS template;

[0030] Figure 3 (ac) SEM images and (df) elemental mapping images of the prepared SOM-Ce;

[0031] Figure 4 is the EIS spectrum of Li2S / SOM-Ce;

[0032] Figure 5 for Figure 4 CV graph of Li2S / SOM-Ce;

[0033] Figure 6 This is the charge and discharge curve of Li2S / SOM-Ce at 0.1C. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment: In this scheme, the preparation method of the porous carbon material for the positive electrode of the lithium-sulfur battery mainly includes the preparation of PS and the preparation of SOM-Ce.

[0036] Embodiment 1:

[0037] 1. Preparation of PS:

[0038] (1) Add 50 ml of styrene and 15 ml of 15% sodium hydroxide solution into a 150 ml separatory funnel, shake vigorously to make them completely contact, remove the lower aqueous solution, and keep the upper oil solution to remove the inhibitor and acidic impurities therein, and then repeatedly wash with distilled water 3-5 times, 50 ml each time, to remove the residual sodium hydroxide;

[0039] (2) Add the cleaned styrene into a 1000 mL three-necked flask, add 400 mL of distilled water and 1.7 g of polyvinyl pyrrolidone, the particle size of which is 100-500 nm, stir for 20 min under inert atmosphere bubbling, keep warm at 92° C. for 40 min, and then add 60 mL of 10% potassium persulfate aqueous solution as an initiator. Then stir at 92° C. for 22-26 h at a speed of 400 r / min. The PS filter cake formed by the white suspension after the reaction is filtered and repeatedly washed with water and then dried at 40° C. with air.

[0040] It should be further explained that, in the above process, by precisely controlling the polymerization reaction conditions, PS templates with different particle sizes can be obtained, thereby affecting the pore size and distribution of the MOF material.

[0041] 2. Preparation of SOM-Ce:

[0042] (1) The PS filter cake was immersed in a 4 mmol / L cerium nitrate methanol solution for 2 h and then vacuum dried overnight;

[0043] (2) The PS filter cake was soaked in a methanol solution of zinc nitrate and dimethylimidazole for 6 h, with the amounts of zinc nitrate and dimethylimidazole being 3 g and 4 g, respectively (taking 50 mL of methanol solution as an example), and then vacuum dried overnight;

[0044] (3) The PS filter cake is immersed in a mixed solution of methanol and ammonia water, and strong stirring or ultrasound is applied for a short period of 3-5 minutes to assist its rapid growth and nucleation. It is then allowed to grow at room temperature for 22-26 hours, the solution is vacuum filtered, and then vacuum dried overnight.

[0045] (4) The dried material was stirred in 400 mL of THF solution for 24 h to remove the PS template, then centrifuged at 5000 r / min, 3-5 times, 4-8 min each time, and then placed in a forced air drying oven at 110 °C overnight to completely remove THF. After annealing at 1000 °C, cerium-doped ordered mesoporous MOF-derived carbon material SOM-Ce was obtained.

[0046] After SOM-Ce is compounded with lithium sulfide, it is stirred with a conductive agent and a binder, coated and dried to form uniform electrodes, and then assembled into a lithium-sulfur battery.

[0047] in, Figure 1 This is the SEM image of the PS obtained in Example 1. From the image, the elements, structure and particle size information of the PS can be observed. The PS is in the shape of smooth small spheres with a particle size of 120-180nm, and mainly contains three elements: C, H, and O.

[0048] in, Figure 2 This is the SEM image of the ordered porous cerium-doped MOF grown in the PS template in Example 1. Figure 2 It can be seen that the ordered porous cerium-doped MOF grows in the bulk PS template. The PS template participates in the assembly process of MOF because its surface combines Ce ions and Zn ions during the immersion process. After removing the PS template, evenly distributed and uniformly sized holes are formed on the MOF surface.

[0049] in, Figure 3 is a SEM image of the ordered porous cerium-doped MOF-derived carbon material SOM-Ce in Example 1. Figure 3 It can be seen that SOM-Ce has a regular polyhedral shape with uniformly distributed holes of uniform size on the outside, which is conducive to the loading of active materials and the penetration of electrolytes. High-temperature carbonization helps to improve the conductivity and electrochemical stability of the material. The final content of Ce element in SOM-Ce is 0.4% (atomic ratio), the content of C element is 90.4% (atomic ratio), the content of N element is 4.4% (atomic ratio), and the content of O element is 4.8% (atomic ratio).

[0050] In addition, through Figure 4 The EIS spectrum and Figure 5 It can be seen from the CV test that the SOM-Ce material has excellent performance in terms of electrical conductivity (charge transfer impedance Rct=127Ω) and electrochemical activity (CV peak current response reaches 1.3mA). Figure 5The charge-discharge curves in the figure show that Li2S / SOM-Ce releases high specific capacities of 765, 715, and 698 mAh / g in the first cycle at 0.1C, and the charge-discharge efficiencies in the first three cycles are 93.5%, 97.6%, and 98.9%, respectively, indicating that the addition of Ce effectively improves the utilization of active materials, inhibits the shuttle effect, and improves the electrochemical performance and cycle life of lithium-sulfur batteries. These test results provide strong evidence for the practical application of SOM-Ce materials in lithium sulfide-based lithium-sulfur batteries.

[0051] Embodiment 2:

[0052] 1. Preparation of PS:

[0053] (1) Add 65 ml of styrene and 15 ml of 15% sodium hydroxide solution to a 150 ml separatory funnel, shake vigorously to make them completely contact, remove the lower aqueous solution, and keep the upper oil solution to remove the inhibitor and acidic impurities. Then wash repeatedly with distilled water 3-5 times, 50 ml each time, to remove the residual sodium hydroxide;

[0054] (2) Add the cleaned styrene into a 1000 mL three-necked flask, add 400 mL of distilled water and 2.5 g of polyvinyl pyrrolidone, and stir for 20 min under inert atmosphere bubbling. After keeping at 92°C for 40 min, add 100 mL of 10% potassium persulfate aqueous solution as an initiator. Then stir at 75°C for 22-26 h at a speed of 400 r / min. The PS filter cake formed by the white suspension after the reaction is filtered and repeatedly washed with water and then dried at 40°C by air blowing.

[0055] 2. Preparation of SOM-Ce:

[0056] (1) The PS filter cake was immersed in a methanol solution of cerium nitrate with a concentration of 8 mmol / L for 4 h, and then vacuum dried overnight;

[0057] (2) The PS filter cake was soaked in a methanol solution of zinc nitrate and dimethylimidazole for 8 h, with the amounts of zinc nitrate and dimethylimidazole being 3 g and 4 g, respectively (taking 50 mL of methanol solution as an example), and then vacuum dried overnight;

[0058] (3) Soak the PS filter cake in a mixed solution of methanol and ammonia water, and use strong stirring or ultrasound for a short period of 3-5 minutes to assist its rapid growth and nucleation, and then let it stand at room temperature for 22-26 hours. Vacuum filter the solution and then vacuum dry it overnight;

[0059] (4) The dried material was stirred in 400 mL of THF solution for 24 h to remove the PS template, then centrifuged at 5000 r / min, 3-5 times, 4-8 min each time, and then placed in a forced air drying oven at 110 °C overnight to completely remove THF. After annealing at 1000 °C, cerium-doped ordered mesoporous MOF-derived carbon material SOM-Ce was obtained.

[0060] After SOM-Ce is compounded with lithium sulfide, it is stirred with a conductive agent and a binder, coated and dried to form uniform electrodes, which are then assembled into lithium-sulfur batteries.

[0061] The PS template prepared according to the method of Experimental Example 2 has a particle size of about 250-300nm. Correspondingly, the size of the holes on the cerium-doped ordered mesoporous MOF and SOM-Ce prepared with this larger particle size PS template also increases. Secondly, due to the increase in the concentration of cerium nitrate during immersion, the content of Ce element in SOM-Ce also increases accordingly. Finally, the content of Ce element in SOM-Ce is 0.7% (atomic ratio), the content of C element is 89.9% (atomic ratio), the content of N element is 4.5% (atomic ratio), and the content of O element is 4.9% (atomic ratio). Finally, the electrical conductivity of the SOM-Ce material is the material conductivity (charge transfer impedance Rct = 124Ω).

[0062] Comparative Example 1

[0063] Compared with Example 1, the immersion of Ce methanol solution was removed in the preparation process of Comparative Example 1, and the other steps were the same. The final synthesized sample lacked catalytic centers in the structure due to the lack of Ce element doping, and the first cycle capacity was 634 mAh / g, which was 17% lower than that of Experimental Example 1.

[0064] Comparative Example 2

[0065] Compared with Example 2, Comparative Example 2 did not perform high-temperature sintering during the preparation process, and the remaining steps were the same. The final synthesized sample was not sintered, so the connection between the Ce element and the MOF was not tight enough, and the material conductivity (charge transfer impedance Rct = 151Ω) was much higher than that of Experimental Example 1 (Rct = 127Ω) and Experimental Example 2 (Rct = 124Ω), and the first cycle capacity was 589mAh / g, a decrease of 23%.

[0066] This scheme uses PS templates of different particle sizes to make holes in MOF, and loads Ce elements for modification. Finally, it is carbonized at high temperature to synthesize MOF-derived carbon materials with ordered porous morphology. Its porous structure can accommodate more sulfur / lithium sulfide, the active material of lithium-sulfur batteries, and can also expose more active sites, thereby improving the utilization rate of active centers. Carbonization can improve its structural stability and conductivity, and the EIS spectrum shows its smaller impedance (charge transfer impedance Rct = 127Ω). The Ce atom as the active center can achieve electrochemical activity by receiving and giving electrons due to its unique characteristics (CV peak current response reaches 1.3mA). At the same time, the cerium element has a high polarity and can provide a strong polar adsorption effect, realizing the combination of adsorption + catalytic conversion.

[0067] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous carbon material for a lithium-sulfur battery positive electrode, characterized in that: The following steps are involved: S1, styrene washed with sodium hydroxide and polyvinyl pyrrolidone are polymerized into PS under the condition of oil bath; S2, soaking PS in methanol solution of nitrate and then in methanol solution of zinc nitrate + dimethylimidazole; S3, immersing the treated PS in a mixed solution of methanol and ammonia water to grow MOF; S4. After soaking in THF or DMF and centrifuging to remove PS, a white powder is obtained, and the obtained white powder is annealed in a tube furnace to obtain porous MOF-derived carbon SOM-Ce.

2. The method for preparing a porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: The preparation method of the PS comprises the following steps: S11, 50 mL of styrene and 15 mL of sodium hydroxide were uniformly mixed in a separatory funnel to remove the inhibitor and acidic impurities therein, and then washed with water three times to remove the residual sodium hydroxide; S12, adding the treated styrene into a 1000 mL three-necked flask, adding 400 mL of distilled water and 1.7 g of polyvinyl pyrrolidone, stirring under the condition of bubbling in an inert atmosphere, then keeping warm under the condition of heating in an oil bath, then adding 60 mL of 10% potassium persulfate as an initiator, and performing a polymerization reaction under heating in an oil bath; S13. The white suspension after the polymerization reaction was filtered and washed with distilled water, and then the residual moisture was removed in a 40° C. forced air oven.

3. The method for preparing a porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 2, characterized in that: In S11, the concentration of sodium hydroxide is 5-15%, and the volume ratio of styrene to sodium hydroxide is (1.5-8):1; In S12, the mass ratio of polyvinyl pyrrolidone to potassium persulfate is (2-4):

1.

4. The method for preparing a porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 2, characterized in that: In S12, the bubbling time of the inert atmosphere is 10-30 minutes, the inert atmosphere is argon or nitrogen, and the insulation oil bath time before adding the initiator is 30-60 minutes to ensure the temperature stability in the system.

5. The method for preparing a porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 2, characterized in that: In S12, the heating temperature of the polymerization reaction under oil bath heating is 80-95° C., the reaction time is 22-26 h, and the magnetic stirring speed is 200-600 r / min.

6. The method for preparing a porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: In S2, the ratio of zinc nitrate to dimethylimidazole is 1:(1-1.25), the methanol solution is 50-100 mL, the concentration of nitrate is 0-32 mmol / L, the nitrate includes one or more of cerium nitrate, lanthanum nitrate, indium nitrate, and iron nitrate, and the concentration of nitrate in methanol is 5-50 mg / mL, the immersion time is 2-8 h, and the drying temperature after immersion is 40°C for 8-24 h.

7. The method for preparing a porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: In S3, the ratio of methanol to ammonia water is (0-60 mL): (0-60 mL), and ultrasound is used for 3-5 min to accelerate the nucleation and growth of the MOF material at the beginning of soaking.

8. The method for preparing a porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: In S4, the amount of THF or DMF used is 200-1000 mL, the soaking time is 20-30 h, the solvent for subsequent centrifugation is THF or DMF, the number of centrifugation is 5-6 times, the speed is 5000-6000 r / min, each time is 5-8 min / , the drying temperature is 110°C, and the drying time is 12-24 h.

9. The method for preparing a porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: In S4, the carbonization temperature of the annealing is 800-1000°C, the heating rate is 1-5°C / min, the calcination time is 2-4h, and the atmosphere is argon or nitrogen.

10. A porous carbon material for a lithium-sulfur battery positive electrode, characterized in that: The porous carbon material is prepared according to the method for preparing a porous carbon material for a positive electrode of a lithium-sulfur battery as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • A lithium-sulfur battery cathode carrier material and its preparation method

    CN109904455B

  • Preparation method of monatomic-containing carbon material and application of monatomic-containing carbon material in lithium-sulfur battery

    CN115148977A

  • Lithium-sulfur battery positive electrode material based on Zn / Co-ZIF derived composite carbon material and preparation method and application thereof

    CN116487575A

  • Rare earth monatomic modified nitrogen-doped porous carbon catalyst for lithium-sulfur battery and preparation method of rare earth monatomic modified nitrogen-doped porous carbon catalyst

    CN117154094A

  • La-based MOF derived carbon material modified diaphragm as well as preparation method and application thereof

    CN118399015A